Reclaiming the body and restoring a bodily self in drama therapy: A case study of sensory-focused Trauma-Centred Developmental Transformations for survivors of father–daughter incest. Issue 2 (1st October 2020) - Willemsen, Marc
Survivors of father–daughter incest often suffer from complex trauma and sensory insensitivity, making it difficult to decipher the sensations in the body and experience body ownership, self-location and agency. This case study illustrates how sensory focused, Trauma-Centred Developmental Transformations can help restore or develop a bodily self, desensitize fear-based schemas, revise deeply buried beliefs and extend repertoire.